Assessing gene function in human B cells: CRISPR/Cas9‐based gene editing and mRNA‐based gene expression in healthy and tumor cells. Issue 8 (22nd May 2022) - Nardi, Federica; Pezzella, Laura; Drago, Roberta; Di Rita, Anthea; Simoncelli, Martina; Marotta, Giuseppe; Gozzetti, Alessandro; Bocchia, Monica; Kabanova, Anna
Abstract : Robust methods for manipulation of human B cells, isolated from healthy donors and patients with B cell disorders, has the potential to significantly accelerate B cell research. Our work describes a step‐by‐step protocol to perform electroporation‐based screening of gene function in B cells through the use of Cas9 ribonuclecomplexes and in vitro produced mRNA.